DINÁMICA DEL AGUA DEL SUELO EN DEHESA BAJO DIFERENTES CUBIERTAS VEGETALES. RESULTADOS PRELIMINARES. - Lozano Parra, F. J.; Schnabel, S.; Ceballos Barbancho, A. (Estudios en la Zona no Saturada del Suelo, 2008)
Dehesa ecosystems, characterized by a disperse tree cover of the genus Quercus, constitute a resource of great importance in large parts of SW Iberian Peninsula. Generally these areas are conditioned by their environmental limits such as shallow soils, seasonal and intraannual rainfall variability, which determine the availability of water for plants. The main objective of the present work is the study of soil water dynamics in dehesas, explaining the effect of different vegetation covers and soil characteristics. Soil moisture is determined in 15 stations, distributed in three farms in Extremadura, each of them composed of sensors located at various depths which register soil moisture continuously with a time resolution of 30 minutes. The stations are distributed in open areas (pasture), below the canopy of the shrub Retama sphaerocarpa and below the canopy of Quercus rotundifolia. First results indicate complex soil water dynamics with contrasting situations at sites with the same vegetation cover, and showing that various situations may be produced in the same station during a hydrological year. Furthermore, the largest variations are observed in the upper soil layer, being soil moisture variations lowest at greater depth, independently of the vegetation cover.
Keywords: bajo copa; Dehesa; humedad del suelo; pastizal; Quercus rotundifolia (voyant); retama sphaerocarpa

Soil hydrological response under simulated rainfall in the Dehesa land system (Extremadura, SW Spain) under drought conditions - Cerdà, A.; Schnabel, S. (Earth Surface Processes and Landforms, 1998)
Soil hydrology was investigated in the Guadelperalón experimental watershed in order to determine the inﬂuence of land use and vegetation cover on runoff and inﬁltration within the Dehesa land system. Five soil–vegetation units were selected: (1) tree cover, (2) sheep trials, (3) shrub cover, (4) hillslope grass and (5) bottom grass. The results of the simulated rainfall experiments performed at an intensity of 53·6mm h −1 during one hour on plots of 0·25m 2 , and the water drop penetration time test indicate the importance of water repellency in the Dehesa land system under drought conditions. Low inﬁltration rates (c. 9–44mm h −1 ) were found everywhere except at shrub sites and in areas with low grazing pressure. Soil water repellency greatly reduced inﬁltration, especially beneath Quercus ilex canopies, where fast ponding and greater runoff rates were observed. The low vegetation cover as a consequence of a prolonged drought and grazing pressure, in conjunction with the soil water repellency, induces high runoff rates (15–70 per cent). In spite of this, macropore ﬂuxes were found in different locations, beneath trees, on shrub-covered surfaces, as well as at sites with a dominance of herbaceous cover. Discontinuity of the runoff ﬂuxes due to variations in hydrophobicity causes preferential ﬂows and as a consequence deeper inﬁltration, especially where macropores are developed
Keywords: Dehesa; Drought; hydrophobicity; rainfall simulation; soil hydrology

ESCORRENT~ A SUPERFICIAL EN LAS VERTIENTES DE UNA CUENCA HIDROGRÁFICA EN EL ECOSISTEMA DEHESA. CUENCA DE GUADALPERAL~ N - Ceballos, Antonio; Schnabel, S. (Geographicalia, 1997)
In a sinall catchrnent under tlie deliesa landuse system overland flow production on slopes is investigated. The obtained results show tliat tl-ie determination of tl-ie tlireshold value for tl-ie generation of runoff is complex. Total precipitation and rnaxim~~m intensity in 10 minutes are the principal factors that explain tl-ie production and generatioii of slope runoff
Keywords: dehesa ecosystem; overland flow; slopes

Effect of scale on surface runoff processes - Barbancho, A. C.; Schnabel, S.; Bolinches, C. (CADERNOS DO LABORATORIO XEOLOXICO DE LAXE 21, 1996)
In a small catchment under the so-called dehesa landuse system, the production of surface runoff is investigated at different scales. This includes experiments with simulated rainfall at micro-plots, event-based measurements of overland flow at 17 open plots and 1 closed plot, and discharge production of the catchment and subcatchment. The runoff coefficients of the considered scales form two groups, with low values for the catchment and sub-catchment and high values for the microplots and hillslope plots. The results show that large part of runoff produced at the slopes is infiltrated afterwards at colluvial sites and the valley floors. Furthermore, they indicate the importance of studying at various scales in order to understand the hydrological processes operating in catchments.
The following values have no corresponding Zotero field: periodical: CADERNOS DO LABORATORIO XEOLOXICO DE LAXE 21 pub-location: O CASTRO DE SAMOEDO, 15168 SADA, LA CORUNA, SPAIN
Keywords: ecosystem dehesa; scale; soil erosion; surface runoff